THE REFLECTION OF PERSONAL LIFE IN MEMOIR AND BILDUNGSROMAN WORKS - Kakharova Mohigul Yusufovna (TADQIQOTLAR, 2025)
Abstract. The article analyzes different types of autobiographical works based on Jack London’s “Martin Eden” as a semi-autobiographic Kunstlerroman, a sub-genre  of  the  bildungsroman,  shedding  light  on  the  developmental  phases  of  a protagonist. The point London makes is able to be witnessed throughout the real world and is essentially the case of the impoverished, self-educated, philosophically inclined, and aspiring author who emerges from the depths of societal desolation. Employing personal history, and wisdom to relay a longing narrative reflecting the psyche of an individual, which without a doubt resonated as the heart of an identity once lost. The outcome of these arises London’s approaches towards depicting life and fiction, from personal events to drawing them into a fantastical portrayal showcasing memoirs of metamorphosing from a step-by-step realization shrouded by the fog of introversion.